If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 44 = 4x Solving 44 = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 44 + -4x = 4x + -4x Combine like terms: 4x + -4x = 0 44 + -4x = 0 Add '-44' to each side of the equation. 44 + -44 + -4x = 0 + -44 Combine like terms: 44 + -44 = 0 0 + -4x = 0 + -44 -4x = 0 + -44 Combine like terms: 0 + -44 = -44 -4x = -44 Divide each side by '-4'. x = 11 Simplifying x = 11
| m+7=29 | | 24-6x=y | | 85=5(-5a-3) | | 9x+10=-x+13 | | -6(3x+7)=-18x-42 | | 4m-13=6-3(1-4m) | | 2=4(3y-8)-11y | | 5x+5=9-(5x-5) | | 1/6x12 | | 5m-6-3m= | | 12x^2-19x-18=0 | | 5/12=11/3m-6 | | 9/x=13 | | 3a+9=-3a+5 | | 18x^2-19x-18=0 | | -3y+3=-6y-6 | | 7(c+4)-4c=-18 | | 3a+7=-3a+5 | | 6x-3+2x=13 | | x-7.5x-10=3 | | 19/60=27/35x+5/3 | | 3a+7=3a-5 | | 2x=5(x-13)-1 | | 3a+8=-4a+4 | | 2(3x-1)=10+2 | | 39/5f-5/6=7/30f | | -15x^3+40x=0 | | 25y=5 | | -5+4+8u=43 | | -13(x+2)+5(4x-4)=6(x-6)+10 | | -x-6=16 | | 4*4+3*-2-4*-2= |